Characterization of transection spinal cord injuries by monitoring somatosensory evoked potentials and motor behavior - All, Angelo H. (2020)
Standardization of spinal cord injury (SCI) models is crucial for reproducible injury in research settings and their objective assessments. Basso, Beattie and Bresnahan (BBB) scoring, the traditional behavioral evaluation method, is subjective and susceptible to human error. On the other hand, neuro-electrophysiological monitoring, such as somatosensory evoked potential (SSEP), is an objective assessment method that can be performed continuously for longitudinal studies. We implemented both SSEP and BBB assessments on transection SCI model. Five experimental groups are designed as follows: left hemi-transection at T8, right hemi-transection at T10, double hemi-transection at left T8 and right T10, complete transection at T8 and control group which receives only laminectomy with intact dura and no injury on spinal cord parenchyma. On days 4, 7, 14 and 21 post-injury, first BBB scores in awake and then SSEP signals in anesthetized rats were obtained. Our results show SSEP signals and BBB scores are both closely associated with transection model and injury progression. However, the two assessment modalities demonstrate different sensitivity in measuring injury progression when it comes to late-stage double hemi-transection, complete transection and hemi-transection injury. Furthermore, SSEP amplitudes are found to be distinct in different injury groups and the progress of their attenuation is increasingly rapid with more severe transection injuries. It is evident from our findings that SSEP and BBB methods provide distinctive and valuable information and could be complementary of each other. We propose incorporating both SSEP monitoring and conventional BBB scoring in SCI research to more effectively standardize injury progression.